1983
DOI: 10.1346/ccmn.1983.0310501
|View full text |Cite
|
Sign up to set email alerts
|

Sorption of Trace Constituents from Aqueous Solutions Onto Secondary Minerals. I. Uranium

Abstract: Abstract--Well-characterized American Petroleum Institute clay standards, source clays from The Clay Minerals Society, and other secondary minerals were used to determine the effects of U concentration, temperature, and solution composition on U-sorption properties. Uranium concentrations ranged from about 1.00 x 10 -4 M to 4.00 x 10 7 M, temperatures from 5 ~ to 65~ and solution compositions containing 0.01 M NaCl and 0.01 M NaHCO3. Silica gel efficiently sorbed uranyl carbonate anion complexes. The higher ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
53
0

Year Published

1995
1995
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(59 citation statements)
references
References 16 publications
6
53
0
Order By: Relevance
“…Montmorillonite was found to have a greater selectivity for the uranyl ion than for sodium and potassium ions in the same solutions. Ames et al (1983) found that uranium was strongly sorbed to montmorillonite fiom 0.01 M NaCl solutions but weakly sorbed from 0.01 M NaHC03 solutions in the pH range from 8 to 9.…”
Section: Uraniummentioning
confidence: 97%
See 2 more Smart Citations
“…Montmorillonite was found to have a greater selectivity for the uranyl ion than for sodium and potassium ions in the same solutions. Ames et al (1983) found that uranium was strongly sorbed to montmorillonite fiom 0.01 M NaCl solutions but weakly sorbed from 0.01 M NaHC03 solutions in the pH range from 8 to 9.…”
Section: Uraniummentioning
confidence: 97%
“…Ames et al (1983) report that clinoptilolite has a low affinity for trace levels of uranium in the plH range from 8 to 9 in 0.01 M NaHC03. Doi et al (1975) found that uranium at concentrations of lo4 g per g of 0 ANL-NBS-HS-000019, Rev 00, ICN 1 solution was strongly sorbed onto clinoptilolite from perchlorate solutions in the pH range from 4 to 8.5.…”
Section: Uraniummentioning
confidence: 98%
See 1 more Smart Citation
“…Sorption of uranium and associated metals and metalloids on mineral surfaces in groundwater systems has been proposed to be an important process in uranium roll-front formation (e.g., Nash et al, 1981;Cuney, 2010). Uranium and associated metals and metalloids (As, Se, V, Mo) in the roll-front ores all apparently have the capability of being sorbed by four common classes of highsurface-area minerals in the roll-front systems: (a) clays (Ames et al, 1983;Wang et al, 2011); (b) iron oxyhydroxides (Dzombak and Morel, 1990); (c) manganese oxyhydroxides (Tani et al, 2004;Wang et al, 2012;and Mukherjee et al, 2013), and (d) Fig. 3.…”
Section: Redox and The Formation Of Roll-front Depositsmentioning
confidence: 99%
“…Typical attachment rates for outdoor conditions (aerosol particle concentration (2-7) · 10 4 cm 3 ) were found to be 20-100 h"' [26], corresponding to average attachment times of 40 s to 3 min. For an aerosol particle concentration of only 100 cm" 3 , an attachment time of about 1 hour was observed [27], Of special relevance is the fact, that due to a 112 keV nuclear recoil, the first progeny of the α-emitting nuclide 218 Po, the daughter nuclide 214 Pb, escapes with about 80% probability [28,29] from the particles which have typical median aerodynamic diameters of 50 to 200 nm [28]. In addition, for indoor condition or outdoor situations close to ground, prior to an attachment of the short-lived 222 Rn progenies to aerosol particles, these nuclides may plate-out to nearby-surfaces.…”
mentioning
confidence: 99%